2013
DOI: 10.1021/ja4075002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of Photon Upconversion in Nd3+-Sensitized Core–Shell Nanoparticles

Abstract: A new type of core-shell upconversion nanoparticles which can be effectively excited at 795 nm has been designed and synthesized through spatially confined doping of neodymium (Nd(3+)) ions. The use of Nd(3+) ions as sensitizers facilitates the energy transfer and photon upconversion of a series of lanthanide activators (Er(3+), Tm(3+), and Ho(3+)) at a biocompatible excitation wavelength (795 nm) and also significantly minimizes the overheating problem associated with conventional 980 nm excitation. Important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
529
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 703 publications
(538 citation statements)
references
References 61 publications
6
529
0
3
Order By: Relevance
“…Remarkably, NIR absorption spectra of nanoparticles with an active NaYF 4 :Nd(20%) shell was almost 17 times stronger compared with nanoparticles treated with an inert NaYF 4 shell (Figure 13b–e) 61. Comparison between cell viabilities of Hela cells upon absorbing 800 and 980 nm light (under identical conditions: 5 min illumination at 6 W cm –2 ) showed that the cancer cells remained intact after 800 nm irradiation while almost all the cancer cells were killed with 980 nm illumination (Figure 13f,g).…”
Section: Effects Of Nir Light Power Intensity On the Upconverting Phementioning
confidence: 97%
“…Remarkably, NIR absorption spectra of nanoparticles with an active NaYF 4 :Nd(20%) shell was almost 17 times stronger compared with nanoparticles treated with an inert NaYF 4 shell (Figure 13b–e) 61. Comparison between cell viabilities of Hela cells upon absorbing 800 and 980 nm light (under identical conditions: 5 min illumination at 6 W cm –2 ) showed that the cancer cells remained intact after 800 nm irradiation while almost all the cancer cells were killed with 980 nm illumination (Figure 13f,g).…”
Section: Effects Of Nir Light Power Intensity On the Upconverting Phementioning
confidence: 97%
“…2b). [48][49][50][51] . The results show that even a relatively low doping level (3%) can cause more rapid rise and decay properties (Fig.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…1(a), the classic dual-doped NaYF 4 : 30%Yb, 0.5%Er/ NaYF 4 and the novel tri-doped NaYF 4 : 30%Yb, 0.5%Er, 1%Nd/ NaYF 4 : 20%Nd core/shell UCNPs with the same Yb 3+ and Er 3+ doping concentration, synthesized through the recently reported protocols [19], were used as the representative of Yb-UCNPs and Nd-UCNPs for the in vitro high resolution and rapid scanning microscopy experiments. The nanoparticles, with the size of about 20 nm, were characterized using transmission electronic microscopy and absorption spectra under the same sample concentration.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Nd 3+ was introduced to UCNPs as the new sensitizer because of its strong absorption band around 795 nm, which would induce the minimized heating effect in bio-system [17,18]. Subsequently, the highly efficient cascade energy transfer (ET) process (Nd 3+ →Yb 3+ →Ln 3+ ) were achieved by modulating the core-shell structure and doping concentration [19,20]. Meanwhile, potential deep imaging ability of this novel UCNPs were indicated [18,20,21].…”
Section: Introductionmentioning
confidence: 99%